2022
DOI: 10.1029/2022gb007316
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Silicon Isotope Dynamics in the Laptev Sea and Implications for Nutrient Availability in the Transpolar Drift

Abstract: Realistic prediction of the near‐future response of Arctic Ocean primary productivity to ongoing warming and sea ice loss requires a mechanistic understanding of the processes controlling nutrient bioavailability. To evaluate continental nutrient inputs, biological utilization, and the influence of mixing and winter processes in the Laptev Sea, the major source region of the Transpolar Drift (TPD), we compare observed with preformed concentrations of dissolved inorganic nitrogen (DIN) and phosphorus (DIP), sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 129 publications
(311 reference statements)
7
19
0
Order By: Relevance
“…An increased variability of stratification has been reported in the region for the period after the mid-2000s, with the region of freshwater influence being determined by summer winds in the ice-free areas (Janout et al, 2020); trends in stratification are thus difficult to generalize. Riverine influence is expected to be rather low for most of the stations investigated here, as indicated by surface salinities reported in previous studies (Janout et al, 2020;Laukert et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
“…An increased variability of stratification has been reported in the region for the period after the mid-2000s, with the region of freshwater influence being determined by summer winds in the ice-free areas (Janout et al, 2020); trends in stratification are thus difficult to generalize. Riverine influence is expected to be rather low for most of the stations investigated here, as indicated by surface salinities reported in previous studies (Janout et al, 2020;Laukert et al, 2022).…”
Section: Discussionsupporting
confidence: 60%
“…This leads to a Si isotope fractionation factor from 3.9‰ to 0.53‰ during diatom production (De La Rocha et al, 1997;Frings et al, 2016;Schmidtbauer et al, 2022;Sun et al, 2014;Sutton et al, 2013Sutton et al, , 2018. The Si isotope values of DSi (expressed as δ 30 Si DSi ) in coastal areas are thus generally higher than those of diatoms, ranging from +0.49‰ to +3.82‰ (summarized from around 600 values measured by published data and this study; Cao et al, 2012Cao et al, , 2015Cassarino et al, 2017;Ehlert et al, 2012;Laukert et al, 2022;Zhang et al, 2019;Zhang, Cao, et al, 2020;.…”
Section: Introductionmentioning
confidence: 61%
“…High-latitude systems exhibit even larger seasonal variations. In the Laptev Sea, the δ 30 Si DSi values varied from +0.91 to +3.82 ‰ in summer, while only from +1.48 to +1.74 ‰ in winter (Laukert et al, 2022). Cassarino et al (2017) found that the δ 30 Si DSi values in the Marguerite Bay on the west side of the Antarctic Peninsula increased from +1.5‰ to +2.0‰ in summer.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations